Telling Tales in Troubled Times: Review of Donna J. Haraway, Staying with the Trouble: Making Kin in the Chthulucene - Iveson, Richard (Humanimalia, 2017)
Donna J. Haraway. Staying with the Trouble: Making Kin in the Chthulucene. Experimental Futures. Durham, NC: Duke University Press, 2016. 312 pp. $94.95 (hc); $26.95 (pb).